2008
DOI: 10.1590/s1413-81232008000200019
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the environmental and human health knowledge base of carbon nanotubes

Abstract: Carbon nanotubes (CNTs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
158
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(161 citation statements)
references
References 55 publications
0
158
1
2
Order By: Relevance
“…4,7 However, no studies have focused on the influence of atmospherically relevant aging on the toxicity of CNTs. Bottini et al 65 found that MWCNTs oxidized by concentrated HNO 3 exhibited a stronger cytotoxic effect to human T lymphocytes than fresh MWCNTs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,7 However, no studies have focused on the influence of atmospherically relevant aging on the toxicity of CNTs. Bottini et al 65 found that MWCNTs oxidized by concentrated HNO 3 exhibited a stronger cytotoxic effect to human T lymphocytes than fresh MWCNTs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Although the carcinogenicity of CNTs is presently unclear, it is well-recognized that CNTs are redox active; are capable of causing oxidative stress; and result in inflammation, epitheloid granulomas, fibrosis, and biochemical changes in lungs. 4,7 A negative effect associated with CNTs on the survival of invertebrates 2 and human epithelial cells 9,12 has also been observed due to the formation of reactive oxygen species (ROS). 2,9 In addition, the toxicity of nanoparticles has been found to be dependent upon specific physiochemical factors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In summary, as most existing studies have focused on acute or long-term effects of a single high dose of MWCNTs and have not considered the consequences of a repeated continuous exposure, a comparison with our in vitro results is limited. The outcome of those studies is that most CNTs elicited inflammation, oxidative stress or caused long-term pathological effects such as granulomas and fibrosis (Helland et al, 2007) but due to the different CNT material and suspension procedures used, statements on the biological impact of CNTs in this regard remains an obstacle.…”
Section: Discussionmentioning
confidence: 99%
“…It is suspected that ENP are even too small for defense mechanisms of the body's immune system. Recently, the possibility of non-hindered nanoparticle transfer through the cell membrane directly into cells (Helland et al 2007;Kaiser et al 2008Kaiser et al , 2009Wick et al 2006) has been observed. Studies on the effect of different types of ENP on cell toxicity showed dependency on shape and chemical composition (Brunner et al 2006;Wick et al 2007).…”
Section: Introductionmentioning
confidence: 99%